Анатомічні атласи в загальній парадигмі англомовної медичної лексикографії - Гордієнко, Олена В'ячеславівна; Gordiyenko, O. V.; Гордиенко, Е. В. (My University, 2020)
Стаття присвячена вивченню англомовних анатомічних атласів, як одного з компонентів загальної системи англомовної медичної лексикографії. Мета роботи - вивчити особливості і принципи лексикографування англомовної медичної термінології в анатомічних атласах для визначення їх ролі в англомовній медичній лексикографії, як системи, що функціонує в глобальному науково-технічному просторі. Наукова новизна роботи полягає в тому, що в статті вперше досліджуються питання лексикографування англомовного терміну в анатомічних атласах з їх екстраполяцією на методи і підходи, прийняті в англомовній медичній лексикографії, і пропонуються перспективи їх вдосконалення з урахуванням викликів сучасності. Висновки. Анатомічні атласи є невід'ємною функціональною складовою загальної системи англомовної медичної лексикографії, які пройшли самостійний шлях становлення і розвитку від перших рукописних ескізів до сучасних 3D електронних видань зі своєю чіткою організацією і системною кодифікацією медичних знань; анатомічні атласи виконують конкретні функції і завдання в загальній парадигмі англомовної медичніої термінографії, дотримуючись прийнятих термінографічних норм і вимог до видань такого типу і користуючись методами термінологічної лексикографії. The purpose of the article is to study the features, parameters and principles of lexicographic representation of English medical terminology in anatomical atlases for the determination of their role in English medical lexicography, as a system which is functioning in the global scientific and technical space. To achieve the goal, a complex methodology was used: an analytical review of the literature, which was published within the framework of general theory of lexicography, lexicography for special purposes (LSP lexicography) and English medical lexicography; bibliographic method– for compiling the list of English medical reference books; method of lexicographic analysis – to characterize the parameters and structure of atlases; the method of critical analysis (dictionary criticism) – to study the features of the compilation of anatomical atlases; the method of typological analysis was used to develop the principles of classification of reference books; diachronic approach – for the systematic study of lexicographic processes; methods of comparative and analytical analysis – to systematize the results obtained. The scientific novelty of the work lies in the fact, that the article for the first time examines the issues of lexicographic representation of an English term in anatomical atlases with their extrapolation to methods and approaches which were adopted in English medical lexicography and offers prospects for their improvement, taking into account the challenges of modern times. The obtained results allow to reach the following conclusions: anatomical atlases are an integral functional component of the general system of English medical lexicography, which passed their independent way of formation and development from the first manuscripts to modern 3D electronic editions with their clear organization and systematic codification of medical knowledge; anatomical atlases perform their specific functions and tasks in the general paradigm of English medical terminography, adhering to terminological norms and requirements for creation of such types of reference works and using the methods of terminological lexicography; anatomical atlases function within and under the influence of global scientific and technological progress as an integral part of English medical lexicography as a dynamic system. Статья посвящена изучению англоязычных анатомических атласов, как одного из компонентов общей системы англоязычной медицинской лексикографии. Цель работы – изучить особенности и принципы лексикографирования англоязычной медицинской терминологии в анатомических атласах для определения их роли в англоязычной медицинской лексикографии, как системы функционирующей в глобальном научно-техническом пространстве. Научная новизна работы заключается в том, что в статье впервые исследуются вопросы лексикографирования англоязычного термина в анатомических атласах с их экстраполяцией на методы и подходы, принятые в англоязычной медицинской лексикографии, и предлагаются перспективы их совершенствования с учѐтом вызовов современного времени. Выводы. Анатомические атласы являются неотъемлемой функциональной составляющей общей системы англоязычной медицинской лексикографии, которые прошли самостоятельный путь становления и развития от первых рукописных эскизов к современным 3D электронным изданиям со своей чѐткой организацией и системной кодификацией медицинских знаний; анатомические атласы выполняют конкретные функции и задачи в общей парадигме англоязычной медицинской терминографии, соблюдая принятые терминографические нормы и требования к изданиям такого типа и пользуясь методами терминологической лексикографии.
Anatomy atlases in lsp lexicography paradigm based on english reference works
Анатомические атласы в общей парадигме англоязычной медицинской лексикографии
Keywords: лексикографія; англомовна медична термінологія; медичний словник; анатомічний атлас; фактичний словниковий довідник; критичний аналіз; lexicography; English medical terminology; medical dictionary; anatomic atlas; factual dictionary; critical analysis; лексикография; англоязычная медицинская терминология; медицинский словарь; анатомический атлас; фактический словарный справочник; критический анализ